2012
DOI: 10.4172/2157-7471.1000144
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Alternaria species Associated with Citrus Black Rot in Iran

Abstract: Citrus black rot caused by Alternaria spp. is significant post harvest problem in Iran. The causal agent of black rot was originally identified as A. citri by Ellis and Pierce. The genus Alternaria circumscribes considerable morphological diversity and citrus black rot may be caused by more than one morphospecies in addition to A. citri. Morphological identification of small-spored Alternaria spp. is difficult. Phylogenetic analysis was performed on 7 small-spored Alternaria isolates from black rotted citrus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The rot spreads slowly and the disease is not controlled by pre‐ and postharvest fungicides (Timmer et al., 2003 ). It affects mainly navel oranges, but it can infect all citrus fruits when appropriate condition is prepared (Mojerlou, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rot spreads slowly and the disease is not controlled by pre‐ and postharvest fungicides (Timmer et al., 2003 ). It affects mainly navel oranges, but it can infect all citrus fruits when appropriate condition is prepared (Mojerlou, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rot spreads slowly and the disease is not controlled by pre-and postharvest fungicides . It affects mainly navel oranges, but it can infect all citrus fruits when appropriate condition is prepared (Mojerlou, 2012).Infected fruits ripen well before maturity and some of them fall off before harvest. The optimum conditions for Alternaria infections are temperatures from 23 to 27°C, but still, it can grow…”
mentioning
confidence: 99%
“…Bukar et al [35] who reported that different spoilage types were observed when the healthy oranges were reinoculated with the pure isolates of the pathogens. Mojerlou and Safaie [53] claimed that all Alternaria isolates caused black rot to Navel and Valencia oranges cultivars and significant differences were observed between cultivars and among isolates. Nemsa et al [54] studies the pathogenicity of nine isolates of Alternaria against Fortune mandarin.…”
Section: Discussionmentioning
confidence: 99%
“…Brown spot of citrus, black rot of citrus and stem-end rot are well-known citrus diseases. Among these diseases, black rot caused by Alternaria citri produces brown to black spots on fruit (Mojerlou and Safaie, 2012). Several species of Colletotricum are known to cause important diseases of citrus; the most important disease caused by this pathogen is citrus anthracnose, and the characteristic symptom is the withering of twigs and lesions on fruits and leaves (Guarnaccia et al, 2017).…”
Section: Major Disease Of Citrus In Pakistanmentioning
confidence: 99%